Laba Bersih Sebagai Mediator Pengaruh Total Aset dan Total Liabilitas Terhadap Price to Book Value pada Perusahaan Sub Sektor Farmasi Di Bursa Efek Indonesia - Ali Akbar (Universitas Batanghari, 2022)
This purpose of the research is to know and analyze net profit as mediator of effect to total assets and total liabilities on price to book value at pharmaceutical sub-sector companies in the Indonesia stock exchange. That research is using data of secondary from annual financial statements. The purposive sampling method used with four companies that are sampled at pharmaceutical sub-sector companies in the Indonesia stock exchange period 2015-2019. Data analysis in this research uses path analysis with SPSS software. The resulting research informs : 1) total assets and total liabilities simultaneously have significant effect on net profit, 2) total asset has positive and significant effect on net profit, 3) total liabilities has negative and significant effect on net profit, 4) total assets and total liabilities simultaneously have significant effect on price to book value, 5) total assets has positive and significant effect on price to book value, 6) total liabilities has positive and insignificant effect on price to book value, 7) net profit has positive and insignificant effect on price to book value and 8) indirectly total asset and total liabilities through net profit have insignificant effect on price to book value.